Strategi manajemen dalam meningkatkan kinerja koperasi syariah di era digitalisasi - Rahmawati, Nabilah Putri (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze effective management strategies in improving the performance of Islamic cooperatives in the era of digitalization. Islamic cooperatives play an important role in strengthening the economy of the people through the principles of justice and mutual assistance, but still face challenges in terms of efficiency, innovation, and technology utilization. This study uses a literature review method by examining various scientific sources, such as accredited national journals and research articles relevant to the topic of digitalization of Islamic financial institutions. The results of the study show that the implementation of service digitalization strategies, strengthening digital literacy for administrators and members, and product innovation based on information technology and sharia contracts can improve the operational efficiency and financial transparency of cooperatives. In addition, partnerships with sharia fintech and educational institutions can accelerate sustainable digital transformation. However, there are still obstacles such as limited technological infrastructure, a lack of competent human resources, and challenges in complying with sharia principles in digital innovation. This study recommends the importance of developing a comprehensive digital roadmap and risk management so that sharia cooperatives can compete in the digital economy era in an ethical and sustainable manner.